2021
DOI: 10.1146/annurev-publhealth-090519-093711
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to Care: Telemedicine Across Medical Domains

Abstract: Over the past 20 years, the use of telemedicine has increased exponentially. Its fundamental aim is to improve access to care. In this review, we assess the extent to which telemedicine has fulfilled this promise across medical domains. Additionally, we assess whether telemedicine has improved related health outcomes. Finally, we determine who has benefited from this novel form of health care delivery. A review of the literature indicates that ( a) telemedicine has improved access to care for a wide range of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 91 publications
2
94
0
Order By: Relevance
“…Physicians also use high-resolution imaging cameras to give accurate diagnostic photographs to experts. [ [82] , [83] , [84] , [85] ] 2 Facilitate service to disabled patients Telemedicine facilitates access to services for a patient having disabilities. It also increases access for other groups, such as the elderly, the culturally isolated, and the incarcerated.…”
Section: Telemedicine In Healthcare: Significant Application Areasmentioning
confidence: 99%
“…Physicians also use high-resolution imaging cameras to give accurate diagnostic photographs to experts. [ [82] , [83] , [84] , [85] ] 2 Facilitate service to disabled patients Telemedicine facilitates access to services for a patient having disabilities. It also increases access for other groups, such as the elderly, the culturally isolated, and the incarcerated.…”
Section: Telemedicine In Healthcare: Significant Application Areasmentioning
confidence: 99%
“…This was the case even though telemedicine was never used in the Polish primary healthcare institutions before. 55.5% of the respondents believe that the medical care they received during teleconsultation was as good as meeting their GP face to face [82] The previous studies confirmed that, for some patients, telehealth can be as good as or even better than personal care, especially for those faced with problems concerning physical appointments, e.g., people living in rural areas [83].…”
Section: Discussionmentioning
confidence: 91%
“…Systematic studies have shown that telemedicine has already been successfully used in other countries to provide routine and specialist medical services and has led to greater access to medical care. Moreover, telemedicine has shown similar, and in selected circumstances better, health effects compared to the conventional models of care [83,86], while demonstrating the ability to reduce unnecessary hospitalisations and costs [87].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations